PEMBELAJARAN QUANTUM TEACHING TERHADAP HASIL BELAJAR SISWA KELAS VII SMP KATOLIK SINT ALOYSIUS NIKI-NIKI KABUPATEN TIMOR TENGAH SELATAN - Hildegardis Missa; Anselmus Boy Baunsele (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2021)
This study aims to determine the effect of the Quantum Teaching model on the learning outcomes of seventh grade students of Sint Aloysius Niki-Niki Catholic Middle School. This type of research is quantitative research with a quasi-experimental method and the research design used is the Nonrandomized Control group Pretest-Posttest Design. The population in this study were all seventh grade students of Sint Aloysius Niki-Niki Catholic Middle School. The data analysis technique used descriptive analysis and inferential analysis. The results showed that the post test score in the experimental class that applied the Quantum Teaching model was higher, namely 86.37 compared to the control class who applied the conventional learning model, namely 69.13. Anacova test results show the calculated F value is 0,000 or less than 0.05. This shows that H0 which states that there is no effect of the Quantum Teaching model on the learning outcomes of seventh grade students of Sint Aloysius Niki-Niki Catholic Middle School is rejected and the consequence is that Ha states that there is an effect of the Quantum Teaching model on the learning outcomes of seventh grade students of SMP Catholic Sint Aloysius Niki Niki accepted. The results of the activities of students who took part in the experimental class were also higher at 90%. compared to the control class, namely 86.65%. And the teacher's ability to manage learning in the experimental class is included in the good category, namely 98.91%.